PENGARUH PERSEPSI HARGA, LOKASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi pada Konsumen Mister Burger di Kota Semarang) - Dwi Riyadi, 08.05.51.0014; Basiya, Robertus (Students Journal of Economic and Management, 2012)
Benefit that got with do this gives thinking contribution for manager and watchfulness side furthermore in wisdom taking and decision in the field of trade, economics and marketing. as to aim to analyze price perception influence towards customer satisfaction, to analyze location influence towards customer satisfaction, to analyze service quality influence towards customer satisfaction and to analyze price perception influence, location and service quality towards customer satisfaction. This watchfulness aims to detect to detect price perception influence, location and service quality towards customer satisfaction. as to sample in this watchfulness is sample in this watchfulness customer mister burger at city Semarang. Analyzer that used doubled linear regression. Watchfulness result shows that found influence significant positive between price perception towards customer satisfaction, will mean when achievable price perception so customer satisfaction will increase. The influence significant positive between location towards customer satisfaction, will mean when location will increase so customer satisfaction will increase. Found influence significant positive between service towards customer satisfaction, will mean when service will increase so customer satisfaction will increase.Keywords: Price Perception, Location and Service Quality towards Customer Satisfaction